2000
DOI: 10.1097/00006324-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of the Effect of Single-Vision vs. Bifocal Lenses on Myopia Progression in Children with Esophoria

Abstract: Use of bifocals, instead of single-vision glasses, by children with near-point esophoria seemed to slow myopia progression to a slight degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(122 citation statements)
references
References 13 publications
4
116
2
Order By: Relevance
“…17 Prospective studies also supported this finding. 10,14 However, other studies 8,11,12,18,19 have been unable to demonstrate such an effect. Given that myopic children have been found to have high response accommodation convergence to accommodation ratios, 20 those with orthophoria and exophoria who wear positive lenses will have a significant exophoric shift resulting in a higher demand for positive fusional vergence.…”
mentioning
confidence: 92%
“…17 Prospective studies also supported this finding. 10,14 However, other studies 8,11,12,18,19 have been unable to demonstrate such an effect. Given that myopic children have been found to have high response accommodation convergence to accommodation ratios, 20 those with orthophoria and exophoria who wear positive lenses will have a significant exophoric shift resulting in a higher demand for positive fusional vergence.…”
mentioning
confidence: 92%
“…Indeed, myopic eyes are said to have greater lag of accommodation compared with nonmyopic eyes with resultant hyperopic defocus at near. 49 Clinical trials were conducted using bifocal spectacles [50][51][52] with an aim to reduce the accommodative demand but the results were equivocal with some studies showing benefit and others reporting no significant difference. It was suggested that poor compliance and/or improper alignment of the spectacles might have confounded results.…”
Section: Undercorrectionmentioning
confidence: 99%
“…32 The results suggested that both bifocal and PALs worked well for children with near esophoria and a large lag of accommodation, but they were not really helpful in controlling myopia progression in subjects who had near orthophoria, exophoria, or a small lag of accommodation. [33][34][35][36] To investigate accommodative performance when the subject wore near-addition lenses, Rosenfield and Carrel 37 compared binocular accommodative responses (ARs) to a 40 cm stimulus when the subject was viewing through his distance correction or his distance correction plus +0.75, +1.50, +2.00, or +2.50 D near-addition lens, respectively. They found that the appropriate plus lens which would result in no error of accommodation (no lead or lag) was determined by the subject's initial accommodative error.…”
Section: Dovepressmentioning
confidence: 99%